2019
DOI: 10.3390/molecules24050863
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Photochemical and In Vitro Cytotoxic Evaluation of New Iodinated Aminosquaraines as Potential Sensitizers for Photodynamic Therapy

Abstract: In this work, several benzothiazole-based aminosquaraine dyes, displaying strong absorption within the so-called phototherapeutic window (650–800 nm), were synthesized. The ability, of all the new dyes, to generate singlet oxygen was assessed by determining the correspondent phosphorescence emission and through the comparison with a standard. The quantum yields of singlet oxygen generation were determined and exhibited to be strongly dependent on the nature of the amino substituents introduced in the squaric r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The amines' introduction can thus essentially lead to a significative rise in the cytotoxicity of this dye's core; however, for the dyes presented in this study, it was found that this was intensified in a balanced way. Despite the evidence of a marked increase in cytotoxicity, which proved to be extremely advantageous in the present research, the amines' introduction in this dye's core is of great relevance, since, in addition to allowing an increase in its ability for producing singlet oxygen [77,78], as we verified on a small scale, it favorably increases its uptake by cells due to its cationic character and increases its polarity, thus favoring its interaction with biological systems [79].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The amines' introduction can thus essentially lead to a significative rise in the cytotoxicity of this dye's core; however, for the dyes presented in this study, it was found that this was intensified in a balanced way. Despite the evidence of a marked increase in cytotoxicity, which proved to be extremely advantageous in the present research, the amines' introduction in this dye's core is of great relevance, since, in addition to allowing an increase in its ability for producing singlet oxygen [77,78], as we verified on a small scale, it favorably increases its uptake by cells due to its cationic character and increases its polarity, thus favoring its interaction with biological systems [79].…”
Section: Discussionmentioning
confidence: 67%
“…These values are within those previously observed for unsymmetrical analogs [37,48]; however, it was expected that compounds with the selenium atom exhibit increased capacity for the formation of this reactive oxygen species. This speculation is explained by the fact that symmetrical dyes derived from benzoselenazole have exhibited high singlet oxygen quantum yields (0.05 ≤ Φ ∆ ≤ 0.31) in a previous study [77], which were determined using the same technique. Despite being reported by many as a very relevant property, studies have shown that photosensitizer candidates with low singlet oxygen production capacity can reveal very significant antitumor photodynamic activity [37,48,78].…”
Section: Discussionmentioning
confidence: 94%
“…In this way, these dyes possess a positive charge and a cationic character that may facilitate the cellular uptake. Moreover, the presence of the electron-donating amino group, in addition to improving their solubility in physiological conditions, may increase the rigidity of the central bridge and consequently raising the efficiency of singlet oxygen generation [46].…”
Section: Aminosquarainesmentioning
confidence: 99%
“…A couple of years later, the same group inserted a heavy atom (i.e. iodine) on the benzothiazole ring (4f-j) slightly shifting the absorption (+ 10 nm) towards the NIR region and increasing the singlet oxygen quantum yield [46]. When compared to the non-halogenated analogues, these symmetrical diiodinated benzothiazole aminosquaraines exhibited, in general, lower Growth Inhibition GI 50 values under irradiation.…”
Section: Fig 2 Molecular Structures Of Squaraine Dyesmentioning
confidence: 99%
“…Squaraine dyes are derivative of square acid (3,4-dihydroksycyclobutene-1,2-dion), containing a four-membered ring with two oxygen heteroatoms in the center of the molecule with two substituted aromatic rings. They are characterized by absorption and intensive fluorescence in the visible range, thanks to which they find various applications, e.g., as photovoltaic materials (solar cells), molecular sensors, or probes (labels) in biomedical imaging [ 30 , 31 , 32 , 33 , 34 ]. The big advantage of squaraine dyes is their non-toxicity in the dark but the ability to generate reactive oxygen species (including free radicals) under the influence of light contributes to the death of pathogenic cells, hence, the possibility of their use in medicine, particularly in PDT, which is a non-invasive anti-cancer method [ 34 ].…”
Section: Introductionmentioning
confidence: 99%